QUALITY ASSURANCE OF BOTTLED DRINKING WATER USING THE HAZARD ANALYSIS CRITICAL CONTROL POINT SYSTEM APPROACH - Wilson Kosasih; Lithrone Laricha Salomon; Andrian Andrian; Siti Rohana Nasution; Silvi Ariyanti (SINERGI, 2021)
This paper discusses on implementing the design of a quality assurance system using the Hazard Analysis Critical Control Point HACCP approach. The HACCP is often considered by people who are not familiar as a problematic, complicated system that has to be left to experts. This system focuses on preventive measures by controlling the hazards of the drinking water treatment process to prevent the occurrence of diseases due to poisoned water and maintain product quality. This research was conducted at a bottled drinking water company. This company needs to commit to producing products that are hygienic and safe for consumption. In this study, laboratory testing of the finished goods was intended to determine the conformance quality of the product. The sample test result found the coliform bacteria in the bottled drinking water product. At last, this study developed critical control points in the daily operations by applying the whole HACCP principles based on the latest applicable standards.